‘Why Read Literature?’: Appeasing the Appetite for Play - Pagan, Nicholas Osborne (Taylor & Francis, 2018)
This article begins by questioning the ethical turn in literary studies (Hillis Miller, Attridge) and suggests that this redirection has tended to downplay the importance of what Friedrich Schiller had labelled ‘the play-drive’ (Spieltrieb). Drawing on neuroscientist Jaak Panskepp’s findings concerning the primacy of the play instincts, the article focuses on Wolfgang Iser’s ‘literary anthropology’ and a theory of reading that can describe games played by authors and readers in what, following Freud, may be called a ‘playground’ (Tummelplatz). Iser’s concepts ‘the fictive’ and ‘the imaginary’ are then placed alongside traditional concepts from play theory to explore an extract from Toni Morrison’s The Bluest Eye in which the protagonist plays with and dismembers a doll. This analysis appropriates, in particular, Iser’s ideas in order to highlight the fundamentally playful nature of our engagement with literature.